2014
DOI: 10.1080/00206814.2014.936055
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two multidimensional discrimination diagrams from beach and deep-sea sediments from the Gulf of Mexico and their application to Precambrian clastic sedimentary rocks

Abstract: To cite this article: John S. Armstrong-Altrin (2015) Evaluation of two multidimensional discrimination diagrams from beach and deep-sea sediments from the Gulf of Mexico and their application to Precambrian clastic sedimentary rocks, Two discriminant-function-based multidimensional major-element diagrams for the tectonic discrimination of siliciclastic sediments were recently published from a coherent statistical methodology of log e -ratio transformation and linear discriminant analysis. These diagrams were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(63 citation statements)
references
References 51 publications
0
62
0
1
Order By: Relevance
“…They introduced two sets of diagrams, optimised for either low-silica (35-63 % SiO2) or high-silica rocks (63-95 % SiO2). Both sets were successfully tested on Neogene-Quaternary as well as Precambrian sediments (success rates of 75-100 %) (Verma and Armstrong-Altrin 2013;Armstrong-Altrin 2015). Three different tectonic settings were considered: Continental and ocean island arcs ('Arc'-field), continental collision ('Col'-field) and continental rifting leading to the development of passive margins and intracratonic basins ('Rift'-field) (Fig.…”
Section: Tectonic Settingmentioning
confidence: 99%
“…They introduced two sets of diagrams, optimised for either low-silica (35-63 % SiO2) or high-silica rocks (63-95 % SiO2). Both sets were successfully tested on Neogene-Quaternary as well as Precambrian sediments (success rates of 75-100 %) (Verma and Armstrong-Altrin 2013;Armstrong-Altrin 2015). Three different tectonic settings were considered: Continental and ocean island arcs ('Arc'-field), continental collision ('Col'-field) and continental rifting leading to the development of passive margins and intracratonic basins ('Rift'-field) (Fig.…”
Section: Tectonic Settingmentioning
confidence: 99%
“…Weathering intensity of the source area can be quantified through indices such as chemical index of alteration (CIA = molar[Al 2 O 3 /(Al 2 O 3 + CaO* + Na 2 O + K 2 O)] * 100; Nesbitt & Young, ), plagioclase index of alteration (PIA = molar [(Al 2 O 3 − K 2 O)/(Al 2 O 3 + CaO* + Na 2 O − K 2 O)] * 100; Fedo, Nesbitt, & Young, ), and chemical index of weathering (CIW = molar[Al 2 O 3 /(Al 2 O 3 + CaO* + Na 2 O)] * 100; Cullers, ). The above indices are widely applied in various studies (Armstrong‐Altrin, ; Lee, ; Sun et al, ). Chemical weathering strongly influences the mineralogy and chemical compositions of the sediments by removing labile cations such as Ca 2+ , Na + , and K + relative to residual constituents (Al 3+ and Ti 4+ ) through the conversion of feldspar to clay minerals (Nesbitt & Young, ).…”
Section: Discussionmentioning
confidence: 99%
“…The identification diagrams according to major elements were put forward by Bhatia () and Roser and Korsch (), which had been widely applied to discriminate the tectonic setting of the sedimentary basin. However, these traditional identification diagrams have been used with caution in recent years (Armstrong‐Altrin & Verma, ; Moradi et al, ; Zaid, ) due to their low percentage success rate for tectonic setting identified (Armstrong‐Altrin, ; Armstrong‐Altrin & Verma, ; Verma & Armstrong‐Altrin, , ). Recently, two multimajor elements discriminate plots according to the Cenozoic deposits were put forward by Verma and Armstrong‐Altrin () to identify their tectonic setting.…”
Section: Discussionmentioning
confidence: 99%
“…In general, stronger chemical weathering promotes the dissolution of Na, Mg, Ca and K from source rocks, whereas Al in source rocks is resistant to weathering (Nesbitt and Young, ). Thus, higher CIA values indicate increased chemical weathering intensity on the source rock (Armstrong‐Altrin, ; Armstrong‐Altrin et al ., ; Armstrong‐Altrin and Machain‐Castillo, ). For example, unweathered igneous rocks have CIA values close to 50%, Phanerozoic shales have CIA values from 70 to 75%, and residual clays (kaolinite, chlorite, and gibbsite) have CIA values close to 100% (Nesbitt and Young, , ).…”
Section: Discussionmentioning
confidence: 99%